Sparassidae of China 4. The genus Pseudopoda (Araneae: Sparassidae) in Yunnan Province - Jäger, Peter; Vedel, Vincent (Zootaxa, 2007)
The genus Pseudopoda, Jäger, 2000 is revised for Yunnan Province, China. Fifteen new species are described: Pseudopoda sinapophysis sp. n., Pseudopoda interposita sp. n., Pseudopoda gongschana sp. n., Pseudopoda saetosa sp. n., Pseudopoda contentio sp. n., Pseudopoda amelia sp. n., Pseudopoda yinae sp. n., Pseudopoda roganda sp. n., Pseudopoda cangschana sp. n., Pseudopoda shuqiangi sp. n., Pseudopoda daliensis sp. n., Pseudopoda obtusa sp. n., Pseudopoda rivicola sp. n., Pseudopoda digitata sp. n., Pseudopoda contraria sp. n. The male of Pseudopoda bibulba(Xu and Yin, 2000) and the female of Pseudopoda spiculata (Wang, 1990) are described for the first time. Pseudopoda yunnanensis (Yang and Hu, 2001) comb. n. is transferred from the genus Sinopoda Jäger, 1999. Limits of species groups in Pseudopoda are discussed. Some characters are confirmed to be dependent on size of the spider (e.g., leg formula, ratio between head region and width of posterior eye row).